Removal of reactive azo dye in a sequencing batch reactor effects of total cycle time and anaerobic retention time ratio - Vu Minh Trang
Towards improving treatment of textile wastewater in a Sequencing batch Reactor (SBR), enriched sludge was used and the react phase involved four phases: (I) first aerobic, (II) first anaerobic, (III) second aerobic, and (IV) second anaerobic. In theis study the effect of total cycle and aerobic: anaerobic time ration on the color removal of wastewater containing azo dye C.I. Reactive Red 141 were determined.